Transformation of grade II to grade III rhabdoid-papillary meningioma: Is SRS the culprit?. (12th October 2019) - Christodoulides, Ioannis; Pedro Lavrador, Jose; Vergani, Francesco; Bhangoo, Ranjeev; Gullan, Richard; Ashkan, Keyoumars
Abstract: Objectives: Meningiomas demonstrate specific genetic and epigenetic mutations, whose effect on recurrence and progression is still of limited understanding. Single-fraction stereotactic radiosurgery (SRS) is an established alternative treatment to surgical resection, proven to achieve excellent local disease control with minimal side effects. However, its effects on tumorigenesis and malignant transformation are still uncertain. The published estimated risk ranges from 0.04%-2.6% at 15 years. Design: Case report Subjects: Female patient referred to our neurosurgical service Methods: Retrospective analysis of patient's notes, histopathology reports, clinic letters, MDT decisions and imaging studies Results: This report describes a case of a grade II parafalcine meningioma, that was initially resected with a Simpson 2 clearance, and upon recurrence, was managed with a single dose of SRS. More than 7 years later, the meningioma recurred, and due to its increasing size on follow-up imaging, it was re-resected. Histopathology revealed a grade III rhabdoid-papillary lesion, with local brain invasion. Conclusions: To our knowledge, this was the first report to describe malignant transformation of a grade II to a grade III meningioma following SRS therapy to date. Therefore, considering the recent trend towards SRS-treatment for meningiomas, the treating team should always consider its potential effects on tumorigenesis.